2016
DOI: 10.1063/1.4966579
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved lifetimes of the 21Σu+ state of Na2

Abstract: Lifetimes of partially resolved ro-vibrational levels of the Na 2Σ double well state have been measured for the first time. Ground state sodium dimer molecules in a molecular beam are resonantly excited by the doubled output of a 10 ns pulsed dye laser in the range 333-357 nm. After being allowed to decay for a predetermined time interval, the surviving excited molecules are ionized by 532 nm photons from a delayed Nd:YAG laser and detected in a linear time-of-flight mass spectrometer. By appropriate tuning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The modifications have been described previously in Ref. 16 and even greater detail in Ref. 38 and therefore will not be repeated here.…”
Section: The Level 82 Program Computes the Einstein A Coefficient For...mentioning
confidence: 99%
See 2 more Smart Citations
“…The modifications have been described previously in Ref. 16 and even greater detail in Ref. 38 and therefore will not be repeated here.…”
Section: The Level 82 Program Computes the Einstein A Coefficient For...mentioning
confidence: 99%
“…The potential curves of electronic states up to the Na 2 (3s+5s) dissociation limit for the singlet and triplet electronic states and radiative lifetimes of a band of vibrational levels for various electronic states have been studied using various methods [9][10][11][12][13][14][15][16] . Recent experimental and theoretical studies of the radiative lifetimes of the 2 1 Σ + u state of sodium dimers have been reported using a molecular beam apparatus and pulsed dye lasers with a pump-delayed probe technique by Anunciado et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been small number of lifetime measurements in molecules compared to the lifetime measurements in atoms. There are still lack of excited state lifetime measurements in some important ion-molecules, alkali hydride molecules and alkali dimer ion-pair states [25,26,27,28,29]. In this study we present for the first time lifetime measurement of the vibrational level of the E 3 Π g (v=3) molecular state of I 2 by means of two-step double-resonance pulse excitation spectroscopy.…”
Section: Introductionmentioning
confidence: 95%